Ivabradine for treatment of heart failure. Issue 5 (4th May 2019) - Bocchi, Edimar Alcides; Salemi, Vera Maria Cury
ABSTRACT: Introduction : Heart failure with reduced ejection fraction (HFrEF) is associated with a worse outcome. Heart rate (HR) is related to outcome in HFrEF. Ivabradine selectively inhibits If (funny) channels in a concentration-dependent manner reducing HR. Areas covered : The effects of ivabradine in HF were reviewed. The SHIFT trial results indicated that ivabradine improves chronic HFrEF outcomes, whereas published data suggest that amiodarone, digoxin, or verapamil may not be safe or the safety is controversial in HFrEF patients. In the CONSTATHE-DHF study, ivabradine reduced HR and improved left ventricular (LV) ejection fraction, LV diastolic functions, and right ventricle function in acute decompensated HF (ADHF). In chagasic patients, ivabradine reduced HR and a trend toward reduction in all-cause death was observed with ivabradine ( p = 0.07). In children with HFrEF, ivabradine increased NYHA functional class. The most common side effects with ivabradine are bradycardia, atrial fibrillation, and phosphenes. Ivabradine was approved for HFrEF treatment by the EMA and FDA and seems to be cost-effective in HFrEF treatment. Ivabradine is indicated for HFrEF by the ESC HF Guidelines (IIa) and by the 2016 ACC/AHA/HFSA Guidelines (IIa-B-R). Expert opinion : Published evidences demonstrate that ivabradine improves the outcome of chronic HFrEF and it seems to have a promising role in ADHF.